Fa’aliyatu Istikhdam Thariqatu Ta’allum Al-Lughah Al-Mujtama’ (Community Language Learning) Litarqiyati Maharatul Kalam Lada Thalibat Bi Madrasah SMP Muhammadiyah 2 Karangasem Lamongan jawa Timur - irham rosidin, irham; Halim, Andy Fahmi; Santoso, Budi; Farid (Program Studi Pendidikan bahasa Arab IAIN Langsa, 2024)
The aim of this research is to determine students' Arabic speaking skills using the community language learning method, and to find out the extent of the impact of this method on improving the Arabic speaking skills of female students at SMP Muhammadiyah 2 Karangasem Lamongan, East Java. The research sample in this study was 16 grade 1 female students at SMP Muhammadiyah 2 Karangasem Lamongan, East Java, and the type of research was experimental research, and the research approach the researcher used was a quantitative approach. The research tools that researchers use are direct observation tests and interviews. Research results: This is based on the adjusted value in the pre-test of 58.0625, becoming 71.25 in the post-test. The researcher got the t-statistic result = 10.98, then the researcher set the t-table, then the researcher looked for the results in the list (Df) of the t-table and found the result = 2.94 at 1%, then 2.13 at 5%. And because the t-statistic result = 10.98 is greater than the statistical results of 1% and 5%, it means that Ho is rejected and H₁ is accepted, or the hypothesis of this research is accepted. This means that the application of the community language method has great effectiveness in improving speaking skills in first-grade students at Muhammadiyah School 2 Karangasem Lamongan, East Java.